Determination of Metal ions, Phenols, and NO3-, NO2- in Industrial Wastewater of Al-Dura and Al-Najaf Refinery - Salah Risan, Raja'a; Ali Salih Al-Hamdani, Abbas; Falah Hassan, Zainab (International Journal of Psychosocial Rehabilitation, 2020)
Determination of the proportion of selected metal elements (Fe, Mn, Co, Cu, Cr, Ni, Mo, Pb, Cd ) using a flame absorption spectroscopy device and the spectroscopy of graphite furnace and phenols as free radicals (NO₃⁻, NO₂⁻) using an ultraviolet spectroscopy device in the industrial wastewater of Al-Dura (A) and Al-Najaf (B) refinery before and after entering the treatment units, taking into consideration the varying sampling time (more than separated) and setting the temperature during the drawing of the model and conducting a statistical study of the results reached.